La population et le système social. - Nitti, S.; Worms, René (Paris : Giard & Brière, 1897)
Collectie Vrijzinnige Werkmansbibliotheek
Frans
Monografie
Keywords: Smith, Adam; Malthus, Thomas; Vrijzinnige Werkmansbibliotheek; demografie; economische leerstelsels